Pengaruh Struktur Modal, Manajemen Risiko, Kebijakan Dividen, dan Ukuran Perusahaan terhadap Pertumbuhan Perusahaan pada Perusahaan Perbakan yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2023 - Siti Nurul Hidayati; Hwihanus Hwihanus (Jurnal Mutiara Ilmu Akuntansi, 2025)
This study aims to evaluate the effect of capital structure, risk management, dividend policy, and company size on the growth of banking companies listed on the Indonesia Stock Exchange during the 2019-2023 period. Using a quantitative approach and Partial Least Squares (PLS) analysis method, the research data was obtained from the company's financial statements and the official website of the Indonesia Stock Exchange. The results showed that capital structure has a significant negative effect on risk management, but does not have a significant impact on firm growth. Risk management shows a positive influence on firm growth, although not significant. Dividend policy has a significant negative effect on risk management and has no significant impact on firm growth. On the other hand, firm size shows a significant positive effect on risk management, but not significant on firm growth. These findings emphasize the importance of balance in capital and risk management to support firm growth. This study contributes to the financial management literature and offers practical insights for banking firms, investors, and regulators in an effort to support the growth of the banking sector in Indonesia.